Foamability of natural rubber/polypropylene blend / Hairul Amani Abdul Hamid, Norazura Ibrahim and Raja Roslan Raja Mohamed - Abdul Hamid, Hairul Amani; Ibrahim, Norazura; Raja Mohamed, Raja Roslan (2006)
The effects of natural rubber (NR) compositions on the morphology studies, physical and mechanical properties of foamed polypropylene were studied. Polypropylene/natural rubber (PP/NR) blends compatibilised with N, N-m-phenylenedimaleimide (HVA-2) has been prepared by melt blending in a twin screw extruder followed by hot press, using activated Azodicarbonamide as the chemical blowing agent (CBA). In the addition to the propylene and rubber, the other additives were clay, filler and salicylic acid. The foaming behavior of PP/NR blends were characterised based on morphology studies, density and compression tests. It was found that when the NR composition increased, the densities of materials and cells increased while the average cell size, compressive strength and moduli decreased. These could be due to the increase in the melt strength and polymer elasticity thus resulting in controlled the growth of the nucleus bubbles to form cellular structures. In conclusion, 5% NR composition will produce foamed PP/NR with improved morphological properties such as uniform cells distribution and higher cell density with smaller average cell size. The mechanical properties of the foamed PP/NR were also influenced by the composition of NR in the blend.